Relationship between photosynthetic activity and chlorophyll content in an isolated Quercus ilex L. tree during the year (Photosynthetica, 1998)
The relationship between chlorophyll (Chl) content and net photosynthetic rate (PN) in an isolated Quercus ilex tree, growing inside Villa Pamphili Park in Rome, was explored. The highest Pn was in March, May and September (10.1 umol.m-2.s-1, maximum rate). Pn decreased by 65% (with respect to the yearly maximum) when leaf temperature reached 34ºC, and by 50% when leaf temperature was 9ºC. The highest Chl contents were in April, October [1.47g.kg-1 (d.m.), maximum value], and December. The lowest Chl content was found in July (0.78 g.kg-1). The decrease of PN in July was in close connection with the decrease of Chl content. On the contrary, the high Chl content during winter did not correspond with PN of this season. Discordances between Chl content and PN over the year influenced the regression analysis, which although positive did not show very high correlation coefficients (r=0.79. The high Chl (a+b) content during most of the year indicated that the photosynthetic apparatus remained basically intact also during stress periods.